Effect of liming on soil physicochemical properties and yield of some spring wheat ( Triticum aestivu m L.) cultivars i n acid soils of South Eastern Nigeria - Otie, V.O.; Effa, E.B.; Elemi, E.D.; Aberagi, F.V.; Unagwu, B.O.; Ugwuoju, C.L.; Ezeaku, V.I.; Udo, I.I (ADAN JOURNAL OF AGRICULTURE, 2026)
This study was conducted to evaluate the varietal perfo rmance of some spring wheat cultivars and lime application on soil properties, growth, physiology and yield of wheat under acidic soil condition in Calabar, Nigeria. A factorial experiment was laid in a completely randomized design with three lime rates (0 .0 , 0.5 and 1 .0 ton ha) and four spring wheat cultivars Ima m , Sc. Sahai , Norman and WZ 272 2015 ). Soil physicochemical properties, growth variables, photosynthetically active radiation, yield related and yield attributes were measure d . The pre soil analys is showed that the soil was strongly acidic and characterize by low organic carbon, total nitrogen, available phosphorus and exchangeable bases, but high in exchangeable aluminum. Application of lime significantly p≤0.05) improved soil pH, increased calcium and magnesium availability and reduced p≤0.05) aluminum toxicity at the 0.5 ton ha lime rate . Among the cultivars , WZ 272 2015 and Norman were most p≤0.05) responsive to lime, recording superior performance in growth, spikelet formation, dry matter partitioning, and overall yield at the 0.5 ton ha lime rate. Lime application also enhanced light interception at 4 and 8 WAS and was highest p≤0.05) at 0.5 and 1 0 ton ha in WZ 272 2015 and Norman , compared to the c ontrol (0 .0 ton ha) L iming at 0.5 ton ha could be sufficient to ameliorate soil acidity for soil nutrient availability for enhance d wheat performance in the study location . WZ 272 2015 and Norman are recommended for cultivation in lime amended soils follo wing their adaptability and superior yield responses to acidity .